Effects of daytime versus night‐time cesarean deliveries on Stage II lactogenesis. Issue 4 (5th January 2018) - İlhan, Gülşah; Atmaca, Fatma V.; Çümen, Ayşenur; Zebitay, Ali G.; Güngör, Emre S.; Karasu, Ayşe F. G.
Abstract: Aim: The circadian timing system has a rhythm and one of the roles of this system is the mediation of hormonal and metabolic adaptations to lactation. This study was conducted to determine whether the time to stage II lactogenesis differed in women who underwent cesarean section (CS) in the daytime (DT) or night‐time (NT). Methods: This study was conducted at Süleymaniye Research and Education Hospital between June and December 2016. Two hundred and eighty‐eight mothers who had a cesarean delivery and their healthy singleton neonates were included. Clinical and demographic data of the mothers and neonates, time of initiation of breastfeeding and time to stage II lactogenesis were analyzed according to DT or NT CS groups. Results: There were no statistically significant differences in age, gravida, parity, body mass index, week of gestation at birth, postoperative hemoglobin level, cesarean indications, anesthesia type, previous history of breastfeeding, transfusion need, Apgar scores or birth weight‐height of neonates between the DT and NT CS groups. While the time of initiation of breastfeeding did not differ statistically in terms of DT or NT CS groups, the time to stage II lactogenesis was significantly longer in the NT CS group. Conclusions: NT cesarean delivery is a risk factor for the delayed onset of lactogenesis. The results of this study may be useful to clinical practitioners counseling mothers who undergo NT cesarean delivery.